WHY PRESERVE? : QUESTIONING CENTRAL EUROPEAN ETHNICITY AND THE PRACTICE OF PRESERVING BUILDINGS AND MONUMENTS; OR, CURATING (IN) DECAY - Ryynänen, Max; Kaverina, Ksenia (The Nordic Journal of Aesthetics, 2022)
Our culture of appreciation of old buildings today is a product of the heritage culture of the (broadly speaking) eighteenth-century Central European (white, male, educated) upper class. While we find it pleasant and historically informative to have buildings well preserved, we find the absence of critical questioning of the practice surprisingly absent, although we observe an increasing number of academic discussions in the field of heritage studies, informed by decolonisation, climate change activism, and sustainability issues. Critical artistic practices have too been venturing into heritage and memory politics. The extensive costs of preserving old architecture raise eyebrows mainly only in the far- and alt-right circles, but as late reactions by parts of the global community, such as the attacks on statues as part of the Black Lives Matter movement, signal, there might be a change coming regarding our relationship to the built material past. We offer a reading of the history of the phenomenon, which will make it easier to, first, see it as an ethnic and class construct, and then sketch out a new perspective on its metaphysics, from memory to identity, to discourse. We include voices external to the world of heritage – one that is still run by a privileged group that often claims to speak for others, and whose aims and practices are often, at least for now, accepted by others. We then proceed to discuss what kind of a role a curatorial approach could have in questioning and rethinking the idea of preserving.